A Juridical Review of Legal Protection for Workers within the Social Security System in Indonesia - Shashia Andini Kristianto; Gunardi Lie (JURNAL MAHASISWA YUSTISI, 2026)
Legal protection for workers within the social security system is one form of the state's responsibility in realizing societal welfare as mandated by the constitution. This research aims to analyze juridically the forms of legal protection for workers within the social security system in Indonesia and to examine the effectiveness of its implementation. The research method used is normative legal research with a legislative approach and a conceptual approach. The data sources used include primary, secondary, and tertiary legal materials that are analyzed qualitatively. The research results show that normatively, the legal protection of workers within the social security system has a strong legal basis. Guaranties designed to provide comprehensive protection against various risks faced by the workforce. However, in its implementation, there are still various obstacles, such as the low participation rate, especially in the informal sector, and the suboptimal law enforcement against employers who do not fulfilll their obligations. Based on these results, it can be concluded that although the labor social security system in Indonesia has an adequate legal framework, the effectiveness of legal protection still needs to be improved thru enhanced supervision, strict enforcement of sanctions, and increased awareness and compliance from all parties involved.